Institutional quality role in oil price uncertainty-renewable energy consumption nexus: ASEAN-8 Bayesian evidence - Duy Khanh Le (Center of Biomass & Renewable Energy (CBIORE), 2026)
Amid escalating climate change pressures and global energy market volatility, accelerating the green energy transition is critical yet challenging for developing economies. ASEAN nations face a stark “energy paradox”: rapid economic growth accompanied by heavy reliance on fossil fuels and sluggish renewable energy adoption. Against this backdrop, this study investigates the impact of oil price uncertainty (OPU) on renewable energy consumption in ASEAN-8 countries over the 2002–2022 period and examines the moderating role of institutional quality. We employ a Bayesian linear regression framework using Markov Chain Monte Carlo (MCMC) algorithms, specifically Gibbs sampling, further validated by Feasible Generalized Least Squares (FGLS). This probabilistic approach effectively overcomes small-sample bias, data heterogeneity, and missing data inherent in emerging market datasets. The empirical results reveal that OPU significantly hinders renewable energy consumption, supporting the Real Options Theory wherein market instability compels investors and consumers to defer high-cost, irreversible green projects. Crucially, institutional quality fails to provide the expected moderating effect to shield the green sector from oil market shocks. Furthermore, the findings uncover a critical “institutional paradox”: higher institutional quality adversely correlates with renewable energy adoption, suggesting that improved governance in early-stage ASEAN economies temporarily prioritizes rapid industrialization and traditional fossil-fuel stability over the green transition. As one of the first studies to explore the OPU–renewable energy nexus through a Bayesian lens with institutional moderation, this research challenges conventional assumptions in a heterogeneous region. To achieve Net Zero 2050 targets, ASEAN policymakers must implement decisive green governance reforms and leverage Public-Private Partnerships to attract sustainable capital and decouple regional energy transitions from global commodity shocks.